The Cohesiveness of Veiled Women's Da’wah Communication Group - Arianto Arianto (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2020)
The purpose of this study was to understand the cohesiveness of the da'wah communication of veiled women in the guidance of Islamic teachings. It closely relates the perception of cohesiveness to the sensation component of the collectivity of group members. For example, communication, collectivity, cooperation, common goals, and interdependence of group members. The research method used is descriptive qualitative, case study research type. The subject of the study were 6 female informants, representatives of Hasanuddin University students who wore a veil in their daily life. The collected data were analyzed inductively. The result that the cohesiveness of veiled women's dakwah communication includes aspects of interpersonal communication cohesiveness, commitment cohesiveness, and cohesiveness aspects of achieving common goals. This aspect of cohesiveness focuses his life on life after death. This also makes them have a strong, cooperative, and sincere character together. The cohesiveness of da'wah communication to continually learn with Islam. It veils the research implication of the cohesiveness of women on equality for preaching, da'wah is the purpose of life so it unites them in da'wah efforts.Tujuan penelitian ini adalah untuk memahami kohesifitas komunikasi dakwah kelompok wanita bercadar dalam tuntunan ajaran Islam. Persepsi kohesifias sangat terkait dengan komponen sensasi kolektifitas anggota kelompok. Seperti, komunikasi, kolektifitas, kerjasama, tujuan bersama, dan saling ketergantungan anggota kelompok.  Metode penelitian yang digunakan adalah kualitatif deskriptif, tipe penelitian studi kasus (case study). Subjek penelitian wanita bercadar sebanyak 6 informan, representatif mahasiswi Universitas Hasanuddin yang mengenakan cadar dalam keseharian. Selanjutnya, data yang terkumpul dianalisis secara induktif. Hasil penelitian bahwa kohesivitas komunikasi dakwah wanita bercadar meliputi aspek kohesifitas berkomunikasi interpersonal, aspek kohesifitas berkomitmen, dan aspek kohesifitas pencapaian tujuan bersama. Aspek kohesifitas ini memfokuskan kehidupannya untuk kehidupan sesudah mati. Hal ini juga menjadikan mereka memiliki karakter bersama yang kuat, bekerjsama, dan ikhlas. Kohesifitas komunikasi dakwah dalam upaya keinginan belajar bersama Islam secara terus menerus. Impilikasi penelitian kohesifitas wanita bercadar pada kesamaaan untuk berdakwah, dakwah adalah tujuan hidup sehingga mereka disatukan dalam usaha dakwah.